Soluble CD30 and ELISA‐detected human leukocyte antigen antibodies for the prediction of acute rejection in pediatric renal transplant recipients. (31st December 2012) - Billing, Heiko; Sander, Anja; Süsal, Caner; Ovens, Jörg; Feneberg, Reinhard; Höcker, Britta; Vondrak, Karel; Grenda, Ryszard; Friman, Stybjorn; Milford, David V.; Lucan, Mihai; Opelz, Gerhard; et al.
Summary Biomarker‐based post‐transplant immune monitoring for the prediction of impending graft rejection requires validation in specific patient populations. Serum of 28 pediatric renal transplant recipients within the framework of a well‐controlled prospective randomized trial was analyzed pre‐ and post‐transplant for soluble CD30 (sCD30), a biomarker reflecting mainly T‐cell reactivity, and anti‐human leukocyte antigen (anti‐HLA) antibody reactivity, a biomarker for B‐cell activation. A sCD30 concentration ≥40.3 U/ml on day 14 was able to discriminate between patients with or without biopsy‐proven acute rejection (BPAR) with a sensitivity of 100% and a specificity of 76%. Six of seven patients (86%) with BPAR showed a sCD30 above this cut‐off, whereas only 3/21 patients (14%) without BPAR had a sCD30 above this cut‐off (P = 0.004). For pre‐ and post‐transplant anti‐HLA class II reactivities by enzyme‐linked immunosorbent assay, a cut‐off value of 140 optical density was able to discriminate rejecters from nonrejecters with a sensitivity of 86% or 71% and a specificity of 81% or 90%, respectively. Withdrawal of steroids was associated with a approximately twofold higher serum sCD30 compared to controls, but did not affect anti‐HLA reactivities. An increased post‐transplant sCD30 serum concentration and positive pre‐ and post‐transplant anti‐HLA class II reactivities are informative biomarkers for impending BPAR in pediatric renal transplant recipients. (TWIST, Clinical Trial No: FG‐506‐02‐43)